Gestational diabetes mellitus, prenatal air pollution exposure, and autism spectrum disorder. (December 2019) - Jo, Heejoo; Eckel, Sandrah P.; Chen, Jiu-Chiuan; Cockburn, Myles; Martinez, Mayra P.; Chow, Ting; Lurmann, Frederick W.; Funk, William E.; Xiang, Anny H.; McConnell, Rob
Abstract: Background: Ambient air pollution and maternal diabetes may affect common biological pathways underlying adverse neurodevelopmental effects. However, joint effects of maternal diabetes and air pollution on autism spectrum disorder (ASD) have not been studied. Objective: We evaluated whether prenatal and early-life air pollution exposure interacts with maternal diabetes status to affect ASD risk. Methods: This retrospective cohort study included 246, 420 singleton children born in Kaiser Permanente Southern California hospitals in 1999–2009. Children were followed from birth until age 5, during which 2471 ASD cases were diagnosed. Ozone (O3 ), particulate matter < 2.5 μm (PM2.5 ) and <10 μm in aerodynamic diameter, and nitrogen dioxide measured at regulatory air monitoring stations were interpolated to estimate exposures during preconception and each pregnancy trimester, and first year of life at each child's birth address. Hazard ratios (HRs) for ASD were estimated adjusting for birth year, KPSC service areas, and relevant maternal and child characteristics. For each exposure window, interactions were tested between pollutants and a 4-category maternal diabetes variable (none, GDM ≥ 24 and <24 weeks' gestation, and pre-existing type 2 diabetes). For an exposure window with statistically significant global interaction between pollutant and diabetes (p < 0.05), pollutant-associated HRs were estimated separately for each category of maternal diabetes. Results: There were associations of ASD with preconception, first and third trimesters, and first year of life PM2.5, but not with other pollutants. There were, however, interactions of maternal diabetes with first trimester and first year of life O3 . Increased ASD risk was associated with first trimester O3 among mothers with GDM < 24 weeks' gestation [adjusted HR 1.50 per 15.7 ppb O3 (95% CI: 1.08–2.09)]. No O3 associations with ASD were observed in other categories of maternal diabetes. Conclusions: GDM onset early in pregnancy may increase children's susceptibility to prenatal O3 -associated ASD risk. These novel findings merit further investigation. Highlights: There were interactions of prenatal and early-life exposure to O3 with maternal diabetes. Greater first trimester exposure to O3 was associated with increased risk of ASD only in early onset GDM. No O3 associations with ASD were observed in other categories of maternal diabetes. GDM onset early in pregnancy may increase susceptibility to prenatal O3 -associated ASD risk. These hypothesis-generating findings need to be replicated in future studies.